2017
DOI: 10.1186/s12711-017-0347-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-breed genomic prediction using Bayes R with sequence data and dropping variants with a small effect

Abstract: BackgroundThe increasing availability of whole-genome sequence data is expected to increase the accuracy of genomic prediction. However, results from simulation studies and analysis of real data do not always show an increase in accuracy from sequence data compared to high-density (HD) single nucleotide polymorphism (SNP) chip genotypes. In addition, the sheer number of variants makes analysis of all variants and accurate estimation of all effects computationally challenging. Our objective was to find a strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 24 publications
(47 reference statements)
1
45
0
Order By: Relevance
“…Many studies have shown that inconsistent LD between SNPs and causative variants across populations causes disadvantages compared with using a combined population in genomic prediction [ 5 , 6 , 27 , 28 ]. In this study, the correlation of r LD values of adjacent SNPs with a mean of 0.55 indicated the insufficient consistency in LD between the Beijing and Fujian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that inconsistent LD between SNPs and causative variants across populations causes disadvantages compared with using a combined population in genomic prediction [ 5 , 6 , 27 , 28 ]. In this study, the correlation of r LD values of adjacent SNPs with a mean of 0.55 indicated the insufficient consistency in LD between the Beijing and Fujian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used the local GEBV variance, that combines the effects of variants in a region. Estimating variants effects for full sequence data using a Bayesian model is, however, computationally challenging [15, 16]. Therefore, we used the local GEBV intervals based on HD effects estimated with Bayes R to detect QTL regions, and used the GWAS for the colocalisation analysis and to zoom into sequence level.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the number of common variants to consider increases from tens of thousands to millions without a concomitant increase in phenotypic data points, so too does the curse of dimensionality; that is, it becomes more difficult to accurately estimate the effects of the growing number of SNPs. Although numerical methods have been developed to handle millions of variants 101,[142][143][144][145] , indiscriminate use of whole sequence information has only modestly increased (≤5%) the accuracy of genomic predictions [146][147][148] . Strategies to further improve the accuracy of whole-genome-sequence-based GS currently involve either selecting or assigning more weight to a subset of imputed variants that are more likely to be causative.…”
Section: Increasing the Accuracy Of Gs Using Whole-genome Sequence Immentioning
confidence: 99%